Frequency-reconfigurable triple band antenna for mobile handsets - Behera A.K.; Agarwal M.; Pandey G.; Meshram M.K. (My University, 2025)
A frequency reconfigurable antenna for LTE/WWAN applications is presented in this paper. The proposed antenna operates over triple bands (729 - 984, 1470 - 2200, and 2300 - 2760 MHz) with respect to -6 dB reflection coefficient. The proposed antenna has a compact size of 45 × 17 × 4 mm3. By independently adjusting the ON/OFF states of the two PIN diodes located on the radiating element, the proposed structure can be operated in the PIFA and loop modes. The antenna acts like a planar inverted-F antenna (PIFA) at frequencies in the LTE700 (729 - 806 MHz), GSM850 (824 - 890 MHz), GSM900 (880 - 960 MHz), LTE2300 (2300 - 2400 MHz), and LTE2500 (2500 - 2690 MHz) bands, and like a loop antenna at frequencies in the GSM 1800/1900 (1710 - 1880 MHz, 1850 - 1990 MHz), and UMTS2100 (1920 - 2170 MHz) bands. The antenna characteristics like reflection coefficient and radiation patterns are presented in this paper. © 2015 IEEE.